2022
DOI: 10.3389/fgene.2021.819520
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Biomarker DDOST and Its Correlation With Immune Infiltrates in Hepatocellular Carcinoma

Abstract: Background: Dolichyl-diphosphooligosaccharide–protein glycosyltransferase non-catalytic subunit (DDOST) is an important enzyme in the process of high-mannose oligosaccharide transferring in cells. Increasing DDOST expression is associated with impairing liver function and the increase of hepatic fibrosis degrees, hence exacerbating the liver injury. However, the relation between DDOST and hepatocellular carcinoma (HCC) has not been revealed yet.Method: In this study, we evaluated the prognostic value of DDOST … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
(50 reference statements)
1
12
0
Order By: Relevance
“…Some researchers have shown that patients with skin squamous cell carcinomas that express a high percentage of DDOST have a bad prognosis [16]. Additionally, studies have revealed that DDOST is a separate prognostic factor in people with liver cancer [17]. For the first time, DDOST, which has the highest degree of node among the hub genes with dramatically decreased expression and is enriched in the protein processing in the ER pathway, was linked to CLL in our study.…”
Section: Integrated Protein-protein Interaction (Ppi) Networksupporting
confidence: 53%
“…Some researchers have shown that patients with skin squamous cell carcinomas that express a high percentage of DDOST have a bad prognosis [16]. Additionally, studies have revealed that DDOST is a separate prognostic factor in people with liver cancer [17]. For the first time, DDOST, which has the highest degree of node among the hub genes with dramatically decreased expression and is enriched in the protein processing in the ER pathway, was linked to CLL in our study.…”
Section: Integrated Protein-protein Interaction (Ppi) Networksupporting
confidence: 53%
“…A subunit of the OST complex, DDOST, plays a vital role in N-glycosylation ( 21 ). It has been shown that DDOST also plays an important role in tumors and can serve as a marker for HCC and is closely associated with the TME ( 7 ). Numerous studies on glycomics and glycoproteomics have established a strong link between glycosylation and gliomas ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers found that patients with skin squamous cell carcinoma with highly expressed DDOST showed a worse prognosis ( 6 ). Moreover, studies have shown that DDOST is an independent prognostic factor in patients with liver cancer, and its expression is positively correlated with the level of Th2 cell infiltration, but negatively correlated with the level of cytotoxic cell infiltration ( 7 ). However, no studies have been conducted on DDOST in gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that skewing of the Th1/Th2 cell ratio toward Th2 cells may be associated with HCC metastasis. 38 Further, Th2 cells can induce the polarization of M1 into M2 macrophages, which ultimately leads to suppression of the host immune system, thus promoting cancer development. 39 There is also evidence that energy metabolism between Th2 cells and the tumor microenvironment is interdependent, and can influence tumor development.…”
Section: Discussionmentioning
confidence: 99%